15 INHIBITING EFFECTOR MEMORY T CELLS WITH SHK(L5), A NOVEL PEPTIDE BLOCKER OF THE KV1.3 POTASSIUM CHANNEL. Issue 1 (1st January 2007) - Uemura, M.; Beeton, C.; Matheu, M. P.; Parker, I.; Pennington, M. W.; Cahalan, M. D.; Chandy, K. G.
Abstract : Autoreactive effector memory (TEM ) T lymphocytes play a major role in the pathogenesis of autoimmune diseases. Therefore, therapies that selectively target TEM cells without inducing generalized immunosuppression would have significant value. Blockers of the voltage-gated Kv1.3 K + channel preferentially inhibit TEM cells without impairing the activity of other T cells. In proof-of-concept studies, Kv1.3 inhibitors have been shown to ameliorate disease in six different immune-mediated disorders-multiple sclerosis, type 1 diabetes mellitus, rheumatoid arthritis, bone resorption following periodontitis, contact dermatitis, and delayed-type hypersensitivity (DTH)-without overt signs of toxicity. Here, we describe our progress in dissecting the mechanism by which ShK(L5), a selective Kv1.3 blocker, ameliorates autoimmune diseases. We used an adoptive DTH model system induced by the intraperitoneal injection into Lewis rats of ovalbumin-specific TEM cells engineered to express the marker gene eGFP (OVA-GFP T cells), followed by a challenge with ovalbumin in the pinna of one ear while the other ear received saline. We show that ShK(L5), injected subcutaneously at the time of challenge in the ears and every 24 hours thereafter, significantly reduced ear swelling when compared with vehicle-treated rats. In addition, ShK(L5) inhibited the proliferation of OVA-GFP T cells in vitro. We combined confocal imaging and flow cytometry to characterize the phenotype of the CD4 + CD45RC - CCR7 − OVA-GFP T cells both in vitro and ex vivo. Using two-photon microscopy, we showed that ShK(L5) acts by delaying the extravasation and reducing the motility of TEM cells at the site of inflammation. These findings support previous data, which show that ShK(L5) might have use for the therapy of autoimmune disorders by selectively targeting TEM cells while leaving the bulk of the immune system unimpaired.